Description of Nurses' Knowledge About Early Breastfeeding Initiation in Postpartum Mothers in the Delivery Room of Syekh Yusuf Regional Hospital, Gowa Regency - Asriani Bahar (Jurnal EduHealth, 2023)
Early Breastfeeding Initiation is an Indonesian government program to reduce the infant mortality rate (IMR). IMR in Indonesia shows a figure of 32/1000 live births, which is still far below that of other ASEAN countries. This is thought to be due to various factors, namely the limited number of breastfeeding counselors in health service facilities and the lack of educational, advocacy, and campaign activities related to the implementation of Early Breastfeeding Initiation. Apart from that, the availability of facilities and infrastructure for Maternal and Child Health This research aims to analyze the influence of the role of health workers on the success of implementing Early Breastfeeding Initiation in the maternity room at Sheikh Yusuf Gowa's house. This research used a descriptive observational research type with a survey method, where the author only wanted to describe nurses' knowledge about early breastfeeding initiation. The sampling method involved 33 respondents. Data was collected using a questionnaire technique. If the respondent answered correctly, the value is 1; if wrong, the value is 0. The research results showed that 33 people (100%) had good knowledge. This research shows that respondents with good knowledge have a great influence on Early Breastfeeding Initiation.